Comparison of the Effectiveness of Transcranial Electrical Brain Stimulation and Cognitive Rehabilitation on Working Memory in Students Aged 7–13 Years with Specific Reading Learning Disorder - Ahmadi , Neda; Ghanadzadegan, Hossein Ali; Heidari , Shaban (Psychological Research in Individuals with Exceptional Needs, 2026)
The overall objective of the present study was to compare the effectiveness of transcranial electrical brain stimulation and cognitive rehabilitation on the working memory of students aged 7–13 years with specific reading learning disorder. In terms of purpose, the present study was applied research, and in terms of methodology, it was a quasi-experimental study with a pretest–posttest design and a control group. The statistical population consisted of all 7–13-year-old students with reading learning disabilities in Districts 7 and 10 of Tehran, totaling 1,500 individuals. A total of 45 participants (15 in the experimental group receiving transcranial electrical brain stimulation, 15 in the experimental group receiving cognitive rehabilitation, and 15 in the control group) were selected as the sample using simple random sampling. Data were collected using the N-back test to assess working memory. Multivariate analysis of covariance and the LSD post hoc test were used for data analysis. Transcranial electrical brain stimulation demonstrated greater effectiveness in improving working memory, particularly in reducing response time, compared with the control group, and in some indicators, it also showed superiority over cognitive rehabilitation. Transcranial electrical brain stimulation interventions and cognitive rehabilitation programs can be used as complementary methods for improving the working memory of students aged 7–13 years with specific reading learning disorder.